Pembelajaran Tari Tradisional Penthul Melikan - Arwendis Wijayanti; Lilik Dwi Kurniawati (JURNAL INOVATIF ILMU PENDIDIKAN, 2019)
The objective of this research was to 1) the implementation of traditional Penthul Melikan dance learning in the Penthul Melikan studio and 2) constraints on the learning process of traditional Penthul Melikan dance in the Penthul Melikan studio. The research method used is qualitative descriptive. The subject of this research was dance students aged 4-6 years totaling 10 children and 2 dance trainers. The collecting data technique has conducted by observation, interview and documentation study. The data analysis techniques in this research were qualitative by Miles and Huberman. The research  results has shown that: 1) the implementation of traditional Penthul Melikan dance learning which consists of opening, core and closing activities, dance trainers always give appreciation to the dance movements that children do in praise making it easier for children to receive dance learning and 2) constraints on the learning process of traditional Penthul Melikan dance is weather, communication between child and dance trainers, childrens abilities are different and there are no written results in dance learning. Advice in teaching of traditional Penthul Melikan dance learning in children is dance trainers easily and pleasantly so that children easily catch and imitate dance movementsKeywords: Learning, traditional penthul melikan dance,children age 4-6 years.DOI: http://dx.doi.org/10.23960/jiip.v1i1.18016